Evaluation of the Thermal Effects in Tilting Pad Bearing - G. B. Daniel; K. L. Cavalca (International Journal of Rotating Machinery)
The analysis of thermal effects is of expressive importance in the context of rotordynamics to evaluate the behavior of hydrodynamic bearings because these effects can influence their dynamic characteristics under specific operational conditions. For this reason, a thermohydrodynamic model is developed in this work, in which the pressure distribution in the oil film and the temperature distribution are calculated together. From the pressure distribution, the velocity distribution field is determined, as well as the viscous dissipation, and consequently, the temperature distribution. The finite volume method is applied to solve the Reynolds equation and the energy equation in the thermohydrodynamic model (THD). The results show that the temperature is higher as the rotational speed increases due to the shear rate of the oil film. The maximum temperature in the bearing occurs in the overloaded pad, near the outlet boundary. The experimental tests were performed in a tilting pad journal bearing operating in a steam turbine to validate the model. The comparison between the experimental and numerical results provides a good correlation. The thermohydrodynamic lubrication developed in this assignment is promising to consistently evaluate the behavior of the tilting pad journal bearing operating in relatively high rotational speeds.